SPECIFIC ASPECTS OF EDUCATING THE SPEED QUALITY OF YOUNG VOLLEYBALL PLAYERS (Universal International Scientific Journal, 2026)
This article provides detailed information on the ways to develop the speed qualities of young volleyball players, their specific aspects, and their importance.
Keywords: physical education; sports; healthy